The Effect of Central Amygdala Nitric Oxide in Expression Of Drug Seeking Behaviors - Mahnaz Rahimpour; Manijeh Karami; Mohammad Reza Jalali (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: Previous studies shows L-arginin (nitric oxide precursor) increases conditioned place preference and drug seeking behaviors whereas LG-nitro-arginine methyl ester) L-NAME( as nitric oxide synthase inhibitor decreases this process. In this project, effects of intra-central amygdale bilateral injection of nitric oxide agents on drug-seeking behaviors including rearing, sniffing and compartment entrance were investigated. Method: animals were wistar male rats (200-250 g) which allowed to be recovered after they're being suffered from a surgery by strereotaxis apparatus to be cannulated in coordination of central amygdale nucleus (CeA). CPP was conducted using a five-day schedule of unbiased procedure. Findings: morphine (2.5-10 mg/kg s.c) induced significant drug-seeking behaviors. Naloxone (0.1-0.4 mg/kg i.p) injection pretesting (after conditioning by morphine 7.5 mg/kg) decreased the expression of behaviors. When L-arginine (0.3-3 µgr/rat) injected intra-CeA prior to naloxone (0.4 mg/kg), increased behaviors but L-NAME (0.3-3 µgr/rat) intra-CeA injections prior to L-arginine (0.3 µgr/rat) pretesting, caused significant decreasement of L-arginine response. Conclusion: NO in the CeA may play an important role in the drug seeking behaviors induced of morphine.